1993
DOI: 10.1111/j.1151-2916.1993.tb03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mechanical Material Property Definition for Predicting the Thermomechanical Behavior of Refractory Linings of Teeming Ladles

Abstract: Ladle vessels continue to play a significant role in clean steelmaking. The incorporation of clean-steel practices imposes severe process environments requiring use of stiffer, stronger refractory linings. As a result, concern has been expressed over the structural integrity of the ladle shell because of the large expansion loads imposed by the stronger linings. Appropriate refractory material properties are required in order to develop accurate and dependable analytical prediction of lining behavior. Analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Through the ladle expansion joints of thermo-mechanical stress, the influence of expansion joint on high alumina, magnesia carbon refractory lining heat was researched. 9 The results showed that the reserved expansion joint of 0.6 mm can reduce the stress 23 MPa on the bottom of the ladle in the high aluminum refractory, which effectively reduces the thermal stress produced by ladle lining material. At the same time, it was also pointed out that expansion joint filler clay combined with static compressive stress data should be taken into account and the true value depended on the creep properties of materials.…”
Section: Introductionmentioning
confidence: 95%
“…Through the ladle expansion joints of thermo-mechanical stress, the influence of expansion joint on high alumina, magnesia carbon refractory lining heat was researched. 9 The results showed that the reserved expansion joint of 0.6 mm can reduce the stress 23 MPa on the bottom of the ladle in the high aluminum refractory, which effectively reduces the thermal stress produced by ladle lining material. At the same time, it was also pointed out that expansion joint filler clay combined with static compressive stress data should be taken into account and the true value depended on the creep properties of materials.…”
Section: Introductionmentioning
confidence: 95%